2015
DOI: 10.1126/science.1260825
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cancer risk among tissues can be explained by the number of stem cell divisions

Abstract: Some tissue types give rise to human cancers millions of times more often than other tissue types. Although this has been recognized for more than a century, it has never been explained. Here, we show that the lifetime risk of cancers of many different types is strongly correlated (0.81) with the total number of divisions of the normal self-renewing cells maintaining that tissue's homeostasis. These results suggest that only a third of the variation in cancer risk among tissues is attributable to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

83
1,633
8
25

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,689 publications
(1,749 citation statements)
references
References 148 publications
83
1,633
8
25
Order By: Relevance
“…Thus, the age dependence of cancer is likely driven in large measure by the statistical likelihood over time that a given set of complementary driver mutations occurs within a single normal cell that transforms it into a malignant cancer cell. Recently, the multistage carcinogenesis model has been further refined by Tomasetti & Vogelstein (2015) to show that lifetime risk of a cancer type correlates with total number of normal stem/progenitor cell divisions that maintain homeostasis within the tissue of origin. Two‐thirds of cancers were estimated to be caused by stochastic replication errors in self‐renewing cells within a tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the age dependence of cancer is likely driven in large measure by the statistical likelihood over time that a given set of complementary driver mutations occurs within a single normal cell that transforms it into a malignant cancer cell. Recently, the multistage carcinogenesis model has been further refined by Tomasetti & Vogelstein (2015) to show that lifetime risk of a cancer type correlates with total number of normal stem/progenitor cell divisions that maintain homeostasis within the tissue of origin. Two‐thirds of cancers were estimated to be caused by stochastic replication errors in self‐renewing cells within a tissue.…”
Section: Introductionmentioning
confidence: 99%
“…According to the CSC hypothesis, a small population of normal stem cells requisite for maintaining tissue homeostasis/renewal can initiate a tumor upon acquiring one or more driver mutations (Chandler 2010). Moreover, a recent study (Tomasetti and Vogelstein 2015) has suggested that the lifetime risk of many different types of cancer is strongly correlated with the total number of divisions of these normal self-renewing cells, and that random mutations arising during DNA replication are likely causative for the emergence of CSC. Interestingly, among the different epithelial stem cells analyzed in that study, those derived from the colon were shown to undergo one of the highest numbers of cell divisions.…”
Section: Introductionmentioning
confidence: 99%
“…As with tumors, the incidence of diffuse epithelial hyperplasia was highest in the proximal SI (duodenum) and lowest in the distal intestine (ileum). Diffuse epithelial hyperplasia is a non‐neoplastic lesion that, under chronic wounding, can lead to increased stem cell proliferation, which can promote transformation and carcinogenesis (Cohen & Ellwein, 1990; Cohen, Gordon, Singh, Arce, & Nyska, 2010; Tomasetti & Vogelstein, 2015). Because Cr(VI) flux through intestinal sections well describes the tumor response in the SI, and hyperplasia is a critical preceding event to tumor formation, intestinal flux was used to model hyperplasia incidence from the NTP (2008) 2 year bioassay.…”
Section: Resultsmentioning
confidence: 99%